1955
DOI: 10.1071/bi9550075
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nutrition on the Water Relations of Salmonella Oranienburg

Abstract: The growth rates of Salmonella oranienburg have been determined in four different basal media in which the water activity (a,v) was controlled by addition of salts and by addition of sucrose. In three complex media the lower limit for growth was between 0�94 and 0�95 aw but in a simple defined medium the limiting aw for growth was between 0�96 and 0�97. When an amino acid mixture containing proline and methionine was added to salt-adjusted simple medium, growth occurred at 0�96 aw' Subsequent addition of eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 6 publications
4
44
0
Order By: Relevance
“…1996). Proline is known to be an effective osmoprotectant (Christian 1955), a sink for energy to regulate redox potentials (Saradhi and Saradhi 1991) or a solute that protects macromolecules from denaturation (Rajendrakumar et al. 1994).…”
Section: Resultsmentioning
confidence: 99%
“…1996). Proline is known to be an effective osmoprotectant (Christian 1955), a sink for energy to regulate redox potentials (Saradhi and Saradhi 1991) or a solute that protects macromolecules from denaturation (Rajendrakumar et al. 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Early work by Christian in 1955 showed that, in Sahnonella oranienburg, exogenously provided prolinc could function as an osmoprolectant [14,15]. A large increase in the intracellular concentration of proline was demonstrated by Measures [78] in the enteric bacteria E. coli and S. O'l)himurium when these were subjccted to osmotic stress.…”
Section: Prou and Prop: Uptake Systems For Osmoprotectantsmentioning
confidence: 99%
“…If, however, 1 mM proline was added to the medium, the free glutamate pool decreased to about two thirds of its value in the absence of proline. Growth stimulation by external proline and partly reversion of salt inhibition under conditions of osmotic stress have been observed in a number of enterobacteria [4,7,63,[65][66][67], and proline is accumulated to high concentrations under these conditions. Growth of Salmonella oranienburg occurred at much higher osmolarities in complex media as compared to simple glucose mineral media, and much of this effect was ascribed to several amino acids in the medium, proline being regarded as the most important one [65].…”
Section: Accumulation Of Amino Acidsmentioning
confidence: 99%
“…Growth stimulation by external proline and partly reversion of salt inhibition under conditions of osmotic stress have been observed in a number of enterobacteria [4,7,63,[65][66][67], and proline is accumulated to high concentrations under these conditions. Growth of Salmonella oranienburg occurred at much higher osmolarities in complex media as compared to simple glucose mineral media, and much of this effect was ascribed to several amino acids in the medium, proline being regarded as the most important one [65]. The intracellular proline level was elevated in direct proportion to increases of the osmolarity of the medium, when proline was present [5,7,45,63,64,68].…”
Section: Accumulation Of Amino Acidsmentioning
confidence: 99%